2003
DOI: 10.1124/mol.64.4.876
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nuclear Factor κB in Tumor Necrosis Factor-Regulated Transcription of the Human μ-Opioid Receptor Gene

Abstract: Opioids and their receptors are key players in a cross-talk between the nervous and immune systems. For example, the endogenous opioid system is activated during inflammation as a physiological feedback mechanism to attenuate inflammatory pain. Herein, we report that in primary human T lymphocytes, Raji B cells, U937 monocytes, primary human polymorphonuclear leukocytes, and mature dendritic cells, the proinflammatory cytokine tumor necrosis factor induced -opioid receptor gene transcription. Transcriptional i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
136
3
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 37 publications
3
136
3
3
Order By: Relevance
“…It has been shown that proinflammatory cytokines and nerve growth factor can induce -opioid receptor expression in inflammatory conditions (23,25,26) and may be involved in the transient increase in opiate receptors in OA. One could envisage that proinflammatory cytokines produced locally in the joint act on the nerves to induce receptor expression and a transient analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that proinflammatory cytokines and nerve growth factor can induce -opioid receptor expression in inflammatory conditions (23,25,26) and may be involved in the transient increase in opiate receptors in OA. One could envisage that proinflammatory cytokines produced locally in the joint act on the nerves to induce receptor expression and a transient analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the proinflammatory cytokine TNF induced mor gene transcription in various immune cells, including human T lymphocytes, leukocytes, and mature dendritic cells (Kraus et al 2003). NF-κB was identified to be responsible for TNF-induced mor gene expression through three NF-κB cis elements on the human mor promoter (Kraus et al 2003).…”
Section: Involvement Of Nf-κb In Opioid Receptor Gene Expressionmentioning
confidence: 99%
“…In the previous section, we reviewed the involvement of NF-κB signaling in opioid functions both in immune cells and neuronal cells. This section focuses on the involvement of NF-κB signaling in the transcriptional regulation of opioid receptor genes (Chen et al 2006;Kraus et al 2003;Park and Wei 2003;Wang et al 2004). …”
Section: Involvement Of Nf-κb In Opioid Receptor Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations